Effectiveness of an "Exclusive Intervention Strategy" to increase medical male circumcision uptake among men aged 25-49 years in South Africa - Jonathan M. Grund; Candice M. Chetty-Makkan; Sibuse Ginindza; Reuben Munyai; Helen Kisbey-Green; Mpho Maraisane; Salome Charalambous (BMC, 2018)
Abstract Background South Africa introduced medical male circumcision (MMC) to reduce HIV incidence. Mathematical modeling suggested that targeting MMC services to men aged 20-34 years could provide the most immediate impact on HIV incidence. However the majority of MMCs performed have been among males aged ≤25 years. We evaluated an intervention package to increase MMC uptake among men aged 25-49 years. Methods We conducted a pre-post study to compare the proportion of men (aged 25-49 years) presenting for MMC during the formative (Phase 1) and intervention (Phase 2) phases in Ekurhuleni, Johannesburg, South Africa. The intervention included infrastructure changes that separated adults from adolescents at the MMC site, an exclusive men's health club, adult-specific demand generation materials, and discussions with community members. Results Overall 2817 enrolled in the study with 1601 from Phase 1 and 1216 in Phase 2. A higher proportion of participants aged 25-49 years accessed MMC in Phase 2 compared to Phase 1 (59.4% vs. 54.9%; Prevalence Ratio = 1.08; 95% Confidence Interval: 1.01-1.15; p = 0.019). Participants with multiple partners in the past 12 months in Phase 2 were more likely to access MMC services compared to participants in Phase 1 (unadjusted Odds Ratio, 1.37; 95% CI:1.17-1.61; p < 0.001). After adjusting for age, multiple partners remained a risk factor in Phase 2 (adjusted OR, 1.39; 95% CI: 1.18-1.63; p < 0.001). Conclusions The "Exclusive Intervention Strategy" was associated with a slight increase in the proportion of participants aged 25-49 years accessing MMC services, and an increase in those with HIV risk behaviors, during the intervention phase. These findings may provide important insights to overcoming barriers for accessing MMC services among men aged 25-49 years. Trial registration The study is registered at ClinicalTrials.gov, number NCT02352961.